Pengaruh Media Dakwah Terhadap Motivasi Keislaman Peserta Didik di MTs 29 Jakarta - Muin, M. Tamsil (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2024)
This research aims to investigate the influence of da'wah media on the Islamic motivation of students at MTs 29 Jakarta. The research method used is a quantitative method with a correlational research design. The sample for this research was MTs 29 Jakarta students, totaling 605 respondents, consisting of 269 male and 336 female students. The instrument used was a questionnaire to measure the use of da'wah media and the level of students' Islamic motivation. The collected data was analyzed using simple regression analysis techniques. The results of the research show that there are positive and negative influences from the use of da'wah media with Islamic motivation for students at MTs 29 Jakarta. The implication of this research is the important role of da'wah media in increasing students' Islamic motivation in Islamic educational institutions. This research also provides input for related parties to pay more attention to the use of da'wah media as a means of increasing students' Islamic motivation.